Efficacy and safety of intercostal nerve anastomosis in immediate subpectoral prosthetic breast reconstruction after nipple–areola-sparing mastectomy: a randomized, controlled, open-label clinical study - Juan, Zhang; Liang, Yong-Ping; Shen, Jiang-Lun; Dai, Hao; Zhang, Yang; Yao, De-Shun; Jiang, Run-Xue; Cai, Hai-Feng (Frontiers in Oncology, 2024)
Purpose This aims to investigate the efficacy and safety of intercostal nerve anastomosis among breast cancer patients who undergo immediate subpectoral prosthetic breast reconstruction after nipple–areola-sparing mastectomy. Methods From 2022 to 2023, female patients between the ages of 20 and 60 diagnosed with stage I–IIIA breast cancer, who required and were willing to undergo immediate subpectoral prosthetic breast reconstruction after nipple–areola-sparing mastectomy, were screened and assigned to take the operation with (treatment group) or without (control group) intercostal nerve anastomosis (the nerves with appropriate length and thickness were selected from the 2nd-4th intercostal nerves, which were then dissociated and anastomosed to the posterior areola tissue). A radial incision at the surface projection of the tumor location was used. The patients’ breast local sensation was assessed using Semmes–Weinstein monofilaments before the operation as well as at 10 days, 3 months, and 6 months postoperatively. Furthermore, the patients’ quality of life was evaluated 6 months postoperatively using the EORTC QLQ-C30 questionnaire. Adverse events, operation duration, drainage volume, and the duration of drainage tube carrying time were also monitored and recorded. Results Compared to the pre-operative period, a significant decrease in local sensation was observed 10 days after surgery in both groups. However, the control group showed a significant reduction in sensation at 3 and 6 months postoperatively, while the treatment group showed noticeable recovery. A statistically significant difference (P < 0.001) in local sensation between the pre-operative and post-operative periods was observed at the final follow-up in the two groups. By the time of 3 and 6 months postoperatively, a significant difference was seen in the local sensation between the two groups. Intercostal nerve anastomosis was found to significantly improve the patients’ quality of life, including emotional (P = 0.01), physical (P = 0.04), and social functioning (P = 0.02) and pain (P = 0.04). There were no significant differences in general characteristics (such as age, BMI, and subtypes). Although intercostal nerve anastomosis increased the duration of operation by around 20 min (P < 0.001), it did not affect the volume or duration of postoperative drainage tube usage between the two groups. Conclusion This study indicated that intercostal nerve anastomosis improved the local sensation and quality of life of patients who underwent immediate subpectoral prosthetic breast reconstruction after nipple–areola-sparing mastectomy. Clinical Trial Registration https://www.chictr.org.cn/showproj.html?proj=42487, identifier ChiCTR1900026340.